Pro Web 2.0 mashups remixing data and Web services - Yee, Raymond; SpringerLink (Online service) (Berkeley, CA : Apress, Inc., 2008)
Provides information on building custom mashups using Web 2.0 technologies.
Includes index.
Keywords: Mashups (World Wide Web); Web 2.0.; Web site development; Computer Science; Programming Techniques